Usability and Accessibility of Shoulder Instability and Open Latarjet Surgery OPEMS for Persons With Disabilities - S Shamtej Singh Rana BS; Jacob Sina Ghahremani BA; Ronald Arnold Navarro MD (Journal of Patient Experience)
The Web Content Accessibility Guidelines (WCAGs) provide website development requirements with users’ cognitive/sensory limitations in mind. The purpose of this study was to assess the accessibility and usability of shoulder instability surgery and open Latarjet surgery online patient education materials (OPEMs) for persons with disabilities based on WCAG compliance. OPEMs were evaluated for search engine optimization, content, design, performance, accessibility, overall scores, body text contrast ratios, and compliance error count at increasing WCAG standard levels. Analysis suggested that OPEMs across both search terms scored poorly in WCAG compliance scores and had significant increases in the number of compliance errors as standards became more stringent. These results suggest that orthopedic OPEMs place unnecessary cognitive and physical loads on users with disabilities, warranting greater scrutiny of the availability and accessibility of orthopedic OPEMs.